Pengaruh Atribut Produk dan Promosi Terhadap Minat Beli Konsumen Kota Pariaman di Toko Online Shopee - Suhatman Suhatman; Meri Rahmania Sari; Patria Nagara; Nasfi Nasfi (Jurnal Bisnis, Manajemen, dan Ekonomi, 2020)
This study aims to determine the effect of product attributes and promotions on consumer buying interest in Kota Pariaman at Shopee online shop. The independent variables are product quality (X1), design (X2), features (X3), promotion (X4) and consumer interest (Y). The sample in this study were 97 online shop consumers in Kota Pariaman. The data collected are primary data using interviews / questionnaires and tools for analyzing SPSS data, 2019. The test uses regression analysis Y0 = 4,967- 0,016 X1 +1,671 X2 + 0,291 X3 + 1,540 X4. The results of the test show that partially the product attributes with product quality indicators have no effect, while design indicators, influential features, and promotions have an effect. And Ujif simultaneously product quality, design, features and promotions have a significant effect on consumer interest. With a determination of 68.3%.